Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

Given that Fx)=x2-4 and g(x) = 1- x, find (f - g)(2), if it exists.​

Sagot :

Replace x with 2 in each equation, then subtract g from f:

f(x) = x^2 -4 = 2^2 -4 = 4-4 = 0

g(x) = 1-x = 1-2 = -1

f-g = 0 - -1 = 1

The answer is 1